EFEKTIVITAS SLAWE: Kemudahan Administrasi Era Digital Warga di Kota Bengkulu - Yogopriyatno, Jatmiko; Safitri, Reni (Public Sphere Review, 2024)
Public service delivery in Bengkulu City faces challenges in efficiency and effectiveness. This study aims to analyze the effectiveness of the Electronic Citizen Administration Service System (SLAWE) implemented by the Department of Population and Civil Registration of Bengkulu City. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation. The results indicate that SLAWE has simplified bureaucratic processes and increased service accessibility. However, its effectiveness is hindered by network instability, manual verification processes, and limited operator training, leading to document processing delays. While procedures align with Standard Operating Procedures, improvements are needed to address public confusion and prevent identity fraud. The study concludes that further socialization is necessary to enhance public understanding of SLAWE requirements and effective usage.